Civil Liability of Founders for Incorporation Acts in a Public Shareholding Company - Alsmadi , Mamoon Suliman; GHUNEMAT , HAMDN; kadhim, Ali Akram; ALWAN, MOHAMMED HAMEED; boutosh , Ahmad; Balas, Hashim (Journal of Ecohumanism, 2024)
The study notes that despite regulatory measures on company formations, especially financial companies, an unlawfully established public shareholding company is possible, raising questions about associated consequences. Legislators’ positions on this vary across jurisdictions and time. Therefore, the study aims to clarify the Jordanian legislator’s stance by elucidating civil liability for founders and outlining liability lawsuit provisions. Key findings reveal a legislative gap regarding founders’ liability for actions during incorporation. It is recommended that the legislator introduces specific rules to regulate founders’ liability, especially concerning contracts on behalf of the company.